THE EFFECT OF TEACHING EXPERIENCE AND ORGANIZATIONAL CULTURE ON TEACHER PERFORMANCE: THE MEDIATION ROLE OF WORK MOTIVATION (A STUDY AT HARAPAN IBU ISLAMIC SCHOOL) - Fitriani Andansari; Setyani Dwi Lestari (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2026)
This study was motivated by the phenomenon of inconsistent teacher performance at Sekolah Islam Harapan Ibu (SIHI), where the results of the 2024–2025 internal evaluation showed a performance score in the “Fairly Good” category (3.8), with the lowest scores in the areas of instructional innovation (3.6) and professional participation (3.4). There is a gap where long tenure does not guarantee productivity, as well as the emergence of symptoms of burnout and stagnation in teaching methods among senior teachers. This study aims to empirically analyze the influence of teaching experience and organizational culture on teacher performance, as well as to test the role of work motivation as a mediating variable in this relationship. This explanatory quantitative study employed a census sampling technique involving 87 teachers at SIHI South Jakarta. Data were collected via a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. Testing was conducted through evaluation of the outer model (validity/reliability) and the inner model (R-Square, Q-Square, and bootstrapping). The results of the testing showed that organizational culture has a positive and significant effect on teacher performance (β=0.365; p=0.000) and work motivation (β=0.729; p=0.000). Work motivation was also found to significantly influence performance (β=0.269; p=0.002) and acted as a partial mediator (mediation coefficient=0.196). Conversely, teaching experience does not significantly influence performance (p=0.257) or work motivation (p=0.052). This model exhibits very strong explanatory power with an R-Square value of 0.873 for teacher performance. Schools are advised not to use seniority as the primary parameter in performance evaluations but rather to focus on strengthening an organizational culture based on Islamic values and integrity. Practically, the foundation needs to implement a “Culture Maintenance Program” to uphold religious values, as well as design a periodic feedback system regarding student progress to stimulate teachers' intrinsic motivation.